2019
DOI: 10.1021/acs.langmuir.8b03988
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Size and Surface Chemistry-Dependent Endosomal Uptake of Gold Nanoparticles Using Surface-Enhanced Raman Scattering

Abstract: Surface-enhanced Raman scattering (SERS)based single-cell analysis is an emerging approach to obtain molecular level information from molecular dynamics in a living cell. In this study, endosomal biochemical dynamics was investigated based on size and surface chemistry-dependent uptake of gold nanoparticles (AuNPs) on single cells over time using SERS. MDA-MB-231 breast cancer cells were exposed to 13 and 50 nm AuNPs and their polyadenine oligonucleotide-modified forms by controlling the order and combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The inspection of the SERS spectra reveals that the intensity of the peaks at 501 cm –1 (S–S) and 1130 cm –1 (phospholipid) significantly decreases in all SERS spectra regardless of the cell type used in the study. In the literature, it was shown that the intensity change of the peak at 501 cm –1 could be related to the formation or deformation of endosomes based on cysteine-rich proteins 14 and the intensity decrease at 1130 cm –1 originating from phospholipids could be related to the decreased number of the formed endosomes in the presence of endocytosis inhibitors. 16 Furthermore, in the late steps of the endocytosis, early endosomes mature and late endosomes are formed with the exchange of membrane components, change in the fusion partners, formation of additional intraluminal vesicles (ILVs), drop in the luminal pH, acquisition of lysosomal components, and change in morphology and movement to the perinuclear area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inspection of the SERS spectra reveals that the intensity of the peaks at 501 cm –1 (S–S) and 1130 cm –1 (phospholipid) significantly decreases in all SERS spectra regardless of the cell type used in the study. In the literature, it was shown that the intensity change of the peak at 501 cm –1 could be related to the formation or deformation of endosomes based on cysteine-rich proteins 14 and the intensity decrease at 1130 cm –1 originating from phospholipids could be related to the decreased number of the formed endosomes in the presence of endocytosis inhibitors. 16 Furthermore, in the late steps of the endocytosis, early endosomes mature and late endosomes are formed with the exchange of membrane components, change in the fusion partners, formation of additional intraluminal vesicles (ILVs), drop in the luminal pH, acquisition of lysosomal components, and change in morphology and movement to the perinuclear area.…”
Section: Resultsmentioning
confidence: 99%
“…It has been investigated for its feasibility for intracellular studies since 1991. 11 , 12 The technique was reported to study the intracellular distribution of gold nanoparticles (AuNPs) and their aggregates, 13 time-dependent endocytosis, 14 size- and shape-dependent uptake of nanomaterials, pH changes during endocytosis, 15 endocytosis types, 16 cellular metabolism changes including death mechanisms, 17 , 18 cellular differentiation, 19 mitosis, 20 and DNA damage. 21 All of these studies suggest that the technique has potential for further investigations of intracellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…The term gold glyconanoparticles, which refer to carbohydrate-tailored AuNPs, was brought into existence in 2001 by de la Fuente et al, and the number of research studies to investigate their possible potential in biomedical applications gradually increased. The benefits of AuNPs, including easy synthesis in a variety of shapes and sizes, easy surface modification and control over the ligand density on the surface, water dispersibility, higher storage stability, unique optical features, and lack of cytotoxicity, made them one of the most preferred carriers in several studies. ,, The main aim to work with gold glyconanoparticles is to mimic the naturally present glycocalyx. Understanding the molecular mechanisms between carbohydrate-decorated AuNPs and their cellular surroundings enables control of the glycocalyx and thus design of novel probes, targeting agents, lectin inhibitors, and drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%